2015
DOI: 10.1007/s10509-015-2630-y
|View full text |Cite
|
Sign up to set email alerts
|

A 3D model for α $\alpha$ Gem AB: orbits and dynamics

Abstract: The well-known multiple star system, Castor, and particularly, the [(Aa, Ab), (Ba, Bb)] subsystem, was studied in detail. After a rigorous analysis of the quality controls, a new solution for the visual orbit yielded new values for the different physical and orbital parameters of the system. In addition, a comprehensive investigation of the orbital configuration of the quadruple system allowed us to provide both accurate individual masses and orbital inclinations of the spectroscopic subcomponents, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Noting that the typical separation of the three spectroscopic subsystems from each other is large, Anosova et al (1989) treated Castor as a triple system (A, B, C) for dynamical purposes and showed, based on the limited information then available, that it is gravitationally bound. Subsequent studies, still handicapped by the limited knowledge of many of the orbital properties, have investigated the stability of the various subsystems and the long-term evolution of some of their orbital elements (Beust 2003;Andrade & Docobo 2015;Matvienko et al 2015;Docobo et al 2016). The latter study focused on the possibility that some of the subsystems are undergoing Kozai-Lidov (KL) cycles (Kozai 1962;Lidov 1962), a mechanism that transfers angular momentum between the inner and outer orbits causing oscillations in the inner eccentricities and inclination angles.…”
Section: Constraints On the Dynamics Of The Castor Systemmentioning
confidence: 99%
“…Noting that the typical separation of the three spectroscopic subsystems from each other is large, Anosova et al (1989) treated Castor as a triple system (A, B, C) for dynamical purposes and showed, based on the limited information then available, that it is gravitationally bound. Subsequent studies, still handicapped by the limited knowledge of many of the orbital properties, have investigated the stability of the various subsystems and the long-term evolution of some of their orbital elements (Beust 2003;Andrade & Docobo 2015;Matvienko et al 2015;Docobo et al 2016). The latter study focused on the possibility that some of the subsystems are undergoing Kozai-Lidov (KL) cycles (Kozai 1962;Lidov 1962), a mechanism that transfers angular momentum between the inner and outer orbits causing oscillations in the inner eccentricities and inclination angles.…”
Section: Constraints On the Dynamics Of The Castor Systemmentioning
confidence: 99%